Gas barrier polyamide film

JP7631806B2Active Publication Date: 2025-02-19TOYOBO CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2020562783
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-12
Filing Date
2020-07-29
Publication Date
2025-02-19
Estimated Expiration
2040-07-29

AI Technical Summary

Benefits of technology

【0012】 本発明のガスバリア性ポリアミドフィルムは、ポリアミド6樹脂を主成分として原料の一部がバイオマス由来であるポリアミド樹脂をブレンドすることと特定の製膜条件を採用することで得られた二軸延伸ポリアミドフィルムの少なくとも片方の面に無機薄膜層を積層することで、耐屈曲ピンホールと耐摩擦ピンホール性が同時に優れ、かつガスバリア性の優れたポリアミドフィルムを提供することができる。 また、本発明ではさらに、従来の耐屈曲ピンホール性を向上のために添加したポリアミド系エラストマーと異なり、ダイス内部でポリアミド系エラストマーが劣化することがないので、長時間にわたり、ダイス内面への劣化物の付着やダイスリップ出口への目ヤニの付着を抑制できる。それによって、フィルムの厚み斑の悪化を防止できる。 また、ダイス内面やダイスリップ出口へ劣化物が付着すると厚み斑が悪化するので、生産を止めてダイスのリップを掃除する必要がある。本発明のガスバリア性ポリアミドフィルムは、長時間の連続生産を可能にすることができる。 更に、原料の一部がバイオマス由来であるポリアミド樹脂を使用するので、元来地上にある植物を原料とするため、地上の二酸化炭素の増減に影響を与えない点で環境負荷を低減できる。また、ガスバリア層としてポリ塩化ビニリデンを塗布したフィルムに比べて環境負荷を低減できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631806000006
    Figure 0007631806000006
  • Figure 0007631806000001
    Figure 0007631806000001
  • Figure 0007631806000002
    Figure 0007631806000002
Patent Text Reader

Abstract

[Problem] To provide a gas barrier polyamide film that is exceptional in terms of both flexural pinhole resistance and frictional pinhole resistance, also has exceptional gas barrier properties, and is suitable for applications in packaging materials. In addition, to reduce the environmental load by using a plant-derived resin as a raw material. [Solution] A gas barrier polyamide film characterized in that an inorganic thin-film layer is provided to at least one surface of a biaxially stretched polyamide film containing 99-70 mass% of polyamide 6 resin and 1-30 mass% of a polyamide resin for which at least part of a raw material is derived from a biomass.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon-neutral gas-barrier polyamide film using a biomass-derived raw material, which has excellent impact resistance, bending pinhole resistance, and abrasion pinhole resistance, and also has excellent gas barrier properties. The gas-barrier polyamide film of the present invention is suitable for use as a food packaging film or the like. [Background technology]

[0002] Biaxially oriented films made of aliphatic polyamides, such as polyamide 6, have been widely used as various packaging film materials due to their excellent impact resistance and pinhole resistance.

[0003] Additionally, for liquid-filled packaging of soup, seasonings, and the like, biaxially oriented polyamide films that have been mixed with various elastomers (rubber components) to further improve resistance to pinholes caused by bending and impact resistance are widely used, making them more flexible and improving pinhole resistance.

[0004] As a means for improving the above-mentioned pinhole resistance due to bending, a film in which a polyamide-based elastomer is mixed with an aliphatic polyamide is known (see, for example, Patent Document 1). This film has good pinhole resistance due to bending and impact resistance in a low-temperature environment, and is less likely to develop pinholes due to bending fatigue even in a low-temperature environment.

[0005] However, pinholes are generated not only by bending but also by friction (abrasion). Methods for improving pinholes caused by bending and pinholes caused by friction are often contradictory. For example, increasing the flexibility of a film makes it less likely for pinholes to occur due to bending, but the softer the film is, the more likely it is that pinholes caused by friction will occur. In response to this, a packaging laminate has been proposed that has excellent resistance to bending and pinholes caused by friction by providing a surface coating agent on the outer surface of a biaxially oriented polyamide film (see, for example, Patent Document 2). However, this method is not very effective at preventing pinholes caused by friction. In addition, a coating process is required. Furthermore, in the case of a film made by mixing aliphatic polyamide with a polyamide-based elastomer, the polyamide-based elastomer added during film production is thermally degraded, and a degraded material called "pit jelly" is easily generated at the exit of the die lip. It was found that the degraded material causes a deterioration in the accuracy of the film thickness. In addition, the degraded material itself falls off, resulting in defective products, which reduces the production efficiency during continuous film production.

[0006] Meanwhile, transparent gas barrier films in which an inorganic oxide thin film is formed on a biaxially oriented polyamide film have come to be used in a wide range of applications, such as food packaging, pharmaceutical packaging, and electronic device packaging, as packaging materials that allow the contents to be seen and prevent deterioration of the contents due to oxygen and water vapor (see, for example, Patent Document 3). Although gas barrier films are endowed with high gas barrier properties by the inorganic thin film, there has been a problem in that the gas barrier properties are significantly deteriorated if pinholes are formed due to bending or friction.

[0007] Meanwhile, in recent years, the use of biomass as an alternative to fossil fuels as a raw material has been attracting attention in the field of materials in order to build a recycling-oriented society. Biomass is an organic compound that is photosynthesized from carbon dioxide and water, and by using it, it becomes carbon dioxide and water again, making it a so-called carbon-neutral raw material (the amount of carbon dioxide emitted and absorbed in the environment is the same, so the increase in carbon dioxide, a greenhouse gas, can be suppressed). Recently, the practical application of biomass plastics made from these biomass raw materials has progressed rapidly, and there are also attempts to produce polyester, a general-purpose polymer material, from these biomass raw materials.

[0008] For example, Patent Document 4 discloses, in the field of polyester films, a resin composition comprising a polyester composed of diol units and dicarboxylic acid units, the diol component unit being ethylene glycol derived from biomass and the dicarboxylic acid component unit being a dicarboxylic acid derived from petroleum, and the resin composition and film are characterized in that the resin composition contains 50 to 95 mass% of the polyester based on the total mass of the resin composition. According to this technology, even if a polyester is produced using ethylene glycol derived from biomass instead of ethylene glycol obtained from conventional fossil fuels, the polyester can have mechanical properties equivalent to those of a polyester produced using ethylene glycol derived from conventional fossil fuels. Against this background, there is a demand for carbon-neutral polyamide films made from raw materials derived from biomass. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 11-254615 [Patent Document 2] JP 2001-205761 A [Patent Document 3] Japanese Patent Application Publication No. 10-29264 [Patent Document 4] JP 2012-097163 A Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been devised in consideration of the problems of the biaxially oriented polyamide film having improved pinhole resistance due to bending according to the prior art. An object of the present invention is to provide a carbon-neutral biaxially oriented polyamide film using a biomass-derived raw material, which has excellent pinhole resistance due to bending and pinhole resistance due to friction, and has excellent gas barrier properties. [Means for solving the problem]

[0011] That is, the present invention comprises the following: [1] A gas barrier polyamide film, characterized in that it has an inorganic thin film layer on at least one side of a biaxially oriented polyamide film containing 99 to 70 mass% polyamide 6 resin and 1 to 30 mass% polyamide resin at least partly derived from biomass. [2] A gas barrier polyamide film characterized by having an inorganic thin film layer on at least one side of a biaxially oriented polyamide film in which the functional layer (B layer) described below is laminated on at least one side of a base layer (A layer) described below. The base layer (A layer) contains 99 to 70 mass % polyamide 6 resin and 1 to 30 mass % polyamide resin at least partly derived from biomass, and the functional layer (B layer) contains 70 mass % or more polyamide 6 resin. [3] The radioactive carbon (C) relative to the total carbon in the biaxially oriented polyamide film 14 2. The gas barrier polyamide film according to claim 1, wherein the content of carbon derived from biomass is 1 to 15% as measured by a carbon sieve analysis. [4] The gas barrier polyamide film according to [1] or [2], wherein the polyamide resin, at least a part of which is derived from biomass, is at least one polyamide resin selected from the group consisting of polyamide 11, polyamide 410, polyamide 610, and polyamide 1010. [5] The gas barrier polyamide film according to [1] or [2], which satisfies the following (a) and (b): (a) The number of Gelbo pinhole defects is 10 or less when a twisting and bending test is performed 1,000 times at a temperature of 1°C using a Gelbo flex tester. (b) In the abrasion pinhole resistance test, the distance until pinholes appear is 2,900 cm or more. [6] The gas barrier laminate film according to [1] or [2], wherein the inorganic thin film layer is a layer made of aluminum oxide or a composite oxide of silicon oxide and aluminum oxide. [7] A laminated film comprising the gas barrier polyamide film according to [1] or [2] and a sealant film laminated thereon. [8] [7] A packaging bag using the laminated film described in [7]. Effect of the Invention

[0012] The gas barrier polyamide film of the present invention is obtained by blending a polyamide resin, mainly composed of polyamide 6 resin, with a polyamide resin partly derived from biomass as a raw material, and by employing specific film-forming conditions to obtain a biaxially oriented polyamide film, on at least one side of which an inorganic thin film layer is laminated. This makes it possible to provide a polyamide film that has excellent bending pinhole resistance and abrasion pinhole resistance as well as excellent gas barrier properties. Furthermore, unlike conventional polyamide-based elastomers added to improve pinhole resistance, the polyamide-based elastomer in the present invention does not deteriorate inside the die, so adhesion of deteriorated materials to the inner surface of the die and adhesion of resin to the outlet of the die lip can be suppressed for a long period of time, thereby preventing the thickness unevenness of the film from worsening. In addition, if deteriorated materials adhere to the inner surface of the die or the outlet of the die lip, the thickness unevenness worsens, so production must be stopped and the die lip must be cleaned. The gas barrier polyamide film of the present invention enables long-term continuous production. Furthermore, since the polyamide resin used is partly derived from biomass, and the raw material is originally from plants that are found on land, it does not affect the increase or decrease of carbon dioxide on land, thereby reducing the environmental impact. In addition, the environmental impact can be reduced compared to films coated with polyvinylidene chloride as a gas barrier layer. [Brief description of the drawings]

[0013] [Figure 1] Schematic diagram of a friction pinhole resistance evaluation device [Explanation of symbols]

[0014] 1: Head of fastness tester 2:Corrugated cardboard 3: Mount for holding samples 4: Film sample folded in four 5: Rubbing amplitude direction DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The gas barrier polyamide film of the present invention will be described in detail below. The gas barrier polyamide film of the present invention is a biaxially oriented polyamide film consisting of 99 to 70 mass% polyamide 6 resin and 1 to 30 mass% polyamide resin at least part of which is derived from biomass, or a biaxially oriented polyamide film consisting of a base layer (A layer) consisting of 99 to 70 mass% polyamide 6 resin and 1 to 30 mass% polyamide resin at least part of which is derived from biomass, and having an inorganic thin film layer on at least one side of the biaxially oriented polyamide film which has a functional layer (B layer) described below laminated on at least one side of the base layer (A layer) consisting of 99 to 70 mass% polyamide 6 resin and 1 to 30 mass% polyamide resin at least part of which is derived from biomass.

[0016] [Biaxially oriented polyamide film or base layer (A layer)] The biaxially oriented polyamide film or base layer (layer A) in the present invention contains 70% by mass or more of polyamide 6 resin, thereby obtaining the excellent mechanical strength such as impact strength and gas barrier properties such as oxygen that are inherent to biaxially oriented polyamide films made of polyamide 6 resin. The biaxially stretched polyamide film or base layer (A layer) in the present invention improves pinhole resistance by containing 1 to 30% by mass of polyamide resin, at least a part of which is derived from biomass. In the case of polyamide-based elastomers and polyolefin-based elastomers, which are conventionally used agents for improving pinhole resistance, pinhole resistance is improved but friction pinhole resistance is deteriorated. By containing 1 to 30% by mass of polyamide resin, at least a part of which is derived from biomass, a biaxially stretched polyamide film having excellent pinhole resistance for bending and pinhole resistance for friction can be obtained. In addition, a carbon-neutral film that is less affected by the increase or decrease in carbon dioxide on the ground can be obtained.

[0017] [Polyamide 6 resin] The polyamide 6 resin used in the present invention is usually produced by ring-opening polymerization of ε-caprolactam. The polyamide 6 resin obtained by ring-opening polymerization is usually subjected to removal of lactam monomer with hot water, followed by drying and melt extrusion in an extruder. Usually, the raw material ε-caprolactam or aminocaproic acid is derived from a fossil fuel. The relative viscosity of the polyamide 6 resin is preferably 1.8 to 4.5, and more preferably 2.6 to 3.2. If the relative viscosity is less than 1.8, the impact strength of the film is insufficient. If the relative viscosity is more than 4.5, the load on the extruder increases, making it difficult to obtain an unstretched film before stretching.

[0018] [Polyamide resin made from at least part of biomass-derived raw materials] Examples of the polyamide resin used in the present invention, at least a part of which is derived from biomass, include polyamide 11, polyamide 410, polyamide 610, polyamide 1010, polyamide MXD10 resin, and polyamide 11·6T copolymer resin.

[0019] Polyamide 11 is a polyamide resin having a structure in which monomers having 11 carbon atoms are bonded via amide bonds. Polyamide 11 is usually obtained by using aminoundecanoic acid or undecane lactam as a monomer. In particular, aminoundecanoic acid is a monomer obtained from castor oil, and is therefore desirable from the viewpoint of carbon neutrality. The constituent units derived from these monomers having 11 carbon atoms preferably account for 50% or more of all the constituent units in polyamide 11, more preferably 80% or more, and may even be 100%.

[0020] The polyamide 11 is usually produced by polymerization of the above-mentioned aminoundecanoic acid. The polyamide 11 obtained by polymerization is optionally subjected to removal of lactam with hot water, dried, and then melt-extruded in an extruder. The relative viscosity of polyamide 11 is preferably 1.8 to 4.5, and more preferably 2.4 to 3.2. If the relative viscosity is less than 1.8, the impact strength of the film is insufficient. If the relative viscosity is more than 4.5, the load on the extruder increases, making it difficult to obtain an unstretched film before stretching.

[0021] The polyamide 610 is a polyamide resin having a structure in which a diamine having 6 carbon atoms and a dicarboxylic acid having 10 carbon atoms are polymerized. Usually, hexamethylenediamine and sebacic acid are used. Of these, sebacic acid is a monomer obtained from castor oil, and is therefore desirable from the viewpoint of carbon neutrality. The total of the constituent units derived from these monomers having 6 carbon atoms and the constituent units derived from monomers having 10 carbon atoms in PA610 is preferably 50% or more, more preferably 80% or more, and may be 100% of all the constituent units.

[0022] The above-mentioned polyamide 1010 is a polyamide resin having a structure in which a diamine having 10 carbon atoms and a dicarboxylic acid having 10 carbon atoms are polymerized. Usually, 1,10-decanediamine (decamethylenediamine) and sebacic acid are used in polyamide 1010. Decamethylenediamine and sebacic acid are monomers obtained from castor oil, and are therefore desirable from the viewpoint of carbon neutrality. The total of the structural units derived from these diamines having 10 carbon atoms and the structural units derived from dicarboxylic acids having 10 carbon atoms in PA1010 is preferably 50% or more, more preferably 80% or more, and may be 100% of all the structural units.

[0023] The above-mentioned polyamide 410 is a polyamide resin having a structure in which a monomer having 4 carbon atoms is copolymerized with a diamine having 10 carbon atoms. Usually, sebacic acid and tetramethylenediamine are used for polyamide 410. From an environmental perspective, it is preferable that the sebacic acid is made from castor oil, a vegetable oil. The sebacic acid used here is preferably made from castor oil from the viewpoint of environmental protection (especially from the viewpoint of carbon neutrality).

[0024] In the biaxially stretched polyamide film or base layer (A layer) of the present invention, the upper limit of the content of the polyamide resin at least partly derived from biomass is 30% by mass, more preferably 20% by mass. If the content of the polyamide resin at least partly derived from biomass exceeds 30% by mass, the molten film becomes unstable when cast, making it difficult to obtain a homogeneous unstretched film.

[0025] [Secondary materials, additives] The biaxially oriented polyamide film or base layer (A layer) in the present invention may contain various additives such as other thermoplastic resins, lubricants, heat stabilizers, antioxidants, antistatic agents, antifogging agents, UV absorbers, dyes, pigments, etc., as necessary.

[0026] <Other thermoplastic resins> The biaxially stretched polyamide film or base layer (A layer) in the present invention may contain a thermoplastic resin in addition to the above-mentioned polyamide 6 and polyamide resin at least part of which is derived from biomass, provided that the object of the present invention is not impaired. Examples of such polyamide resins include polyamide 12 resin, polyamide 66 resin, polyamide 6·12 copolymer resin, polyamide 6·66 copolymer resin, and polyamide MXD6 resin. If necessary, thermoplastic resins other than polyamides, for example, polyester polymers such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate, and polyolefin polymers such as polyethylene and polypropylene, may be contained. It is preferable that the raw materials for these thermoplastic resins are derived from biomass, since they do not affect the increase or decrease in carbon dioxide on the ground and therefore the environmental load can be reduced.

[0027] <Lubricant> In the present invention, the biaxially oriented polyamide film or the base layer (A layer) preferably contains fine particles or an organic lubricant such as a fatty acid amide as a lubricant in order to improve the slipperiness and make it easy to handle. The biaxially oriented polyamide film of the present invention has an effect of reducing breakage of packaging bags due to friction by improving the slipperiness.

[0028] The fine particles can be appropriately selected from inorganic fine particles such as silica, kaolin, zeolite, etc., polymeric organic fine particles such as acrylic and polystyrene, etc. From the viewpoints of transparency and lubricity, it is preferable to use silica fine particles. The average particle size of the fine particles is preferably 0.5 to 5.0 μm, more preferably 1.0 to 3.0 μm. If the average particle size is less than 0.5 μm, a large amount of the fine particles is required to obtain good slip properties. On the other hand, if the average particle size is more than 5.0 μm, the surface roughness of the film tends to become too large, resulting in poor appearance.

[0029] When the silica fine particles are used, the pore volume of the silica is preferably in the range of 0.5 to 2.0 ml / g, more preferably 0.8 to 1.6 ml / g. If the pore volume is less than 0.5 ml / g, voids are likely to occur, resulting in poor transparency of the film, whereas if the pore volume exceeds 2.0 ml / g, the fine particles tend not to form surface protrusions.

[0030] In the present invention, the biaxially stretched polyamide film or the base layer (layer A) may contain fatty acid amide and / or fatty acid bisamide for the purpose of improving the slip property. Examples of fatty acid amide and / or fatty acid bisamide include erucic acid amide, stearic acid amide, ethylene bisstearic acid amide, ethylene bisbehenic acid amide, and ethylene bisoleic acid amide. The content of fatty acid amide and / or fatty acid bisamide in the biaxially stretched polyamide film of the present invention is preferably 0.01 to 0.40% by mass, more preferably 0.05 to 0.30% by mass. If the content of fatty acid amide and / or fatty acid bisamide is less than the above range, the slipping property tends to be deteriorated. On the other hand, if it exceeds the above range, the wettability tends to be deteriorated.

[0031] In the present invention, a polyamide resin such as polyamide MXD6 resin, polyamide 12 resin, polyamide 66 resin, polyamide 6·12 copolymer resin, polyamide 6·66 copolymer resin, etc. can be added to the biaxially stretched polyamide film or base layer (A layer) for the purpose of improving the slip property. In particular, polyamide MXD6 resin is preferred, and it is preferable to add it in an amount of 1 to 10 mass %.

[0032] <Antioxidants> The biaxially oriented polyamide film or the base layer (layer A) in the present invention may contain an antioxidant. The antioxidant is preferably a phenol-based antioxidant. The phenol-based antioxidant is preferably a completely hindered phenol-based compound or a partially hindered phenol-based compound. For example, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, stearyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 3,9-bis[1,1-dimethyl-2-[β-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane, etc. may be mentioned. By adding the phenol-based antioxidant, the film-forming operability of the biaxially oriented polyamide film is improved. In particular, when using recycled film as a raw material, the resin is prone to thermal degradation, which tends to cause film-forming operational problems and increase production costs. In contrast, by adding an antioxidant, the thermal degradation of the resin is suppressed and operability is improved.

[0033] [Functional layer (B layer)] In one embodiment of the present invention, a functional layer (layer B) can be laminated on at least one surface of the base layer (layer A) to improve the surface properties. The layer B is a layer containing 70% by mass or more of polyamide 6 resin. Layer B contains 70% by mass or more of polyamide 6 resin, thereby obtaining a biaxially oriented polyamide film having excellent mechanical strength such as impact strength and gas barrier properties such as oxygen. As the polyamide 6 resin, the same polyamide 6 resin as that used in the above-mentioned layer A can be used.

[0034] Layer B may contain various additives such as other thermoplastic resins, lubricants, heat stabilizers, antioxidants, antistatic agents, anti-fogging agents, UV absorbers, dyes, pigments, etc., depending on the functions to be imparted to the surface of layer B. When layer B is used on the outside of a packaging bag, it needs to be resistant to abrasion and pinholes, so it is undesirable to contain soft resins such as polyamide-based elastomers and polyolefin-based elastomers or substances that generate a large amount of voids.

[0035] Layer B may contain a thermoplastic resin other than the above-mentioned polyamide 6, provided that the object of the present invention is not impaired. Examples of such a polyamide resin include polyamide-MXD6 resin, polyamide 11 resin, polyamide 12 resin, polyamide 66 resin, polyamide 6·12 copolymer resin, and polyamide 6·66 copolymer resin. If necessary, thermoplastic resins other than polyamides, for example, polyester polymers such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate, and polyolefin polymers such as polyethylene and polypropylene, may be contained.

[0036] In order to improve the slipping property of the film, it is preferable that layer B contains fine particles or an organic lubricant as a lubricant. By improving the slipperiness, the film becomes easier to handle and the risk of packaging bags breaking due to friction is reduced.

[0037] The fine particles can be appropriately selected from inorganic fine particles such as silica, kaolin, zeolite, etc., polymeric organic fine particles such as acrylic and polystyrene, etc. From the viewpoints of transparency and lubricity, it is preferable to use silica fine particles.

[0038] The average particle size of the fine particles is preferably 0.5 to 5.0 μm, more preferably 1.0 to 3.0 μm. If the average particle size is less than 0.5 μm, a large amount of the fine particles is required to obtain good slip properties. On the other hand, if the average particle size is more than 5.0 μm, the surface roughness of the film tends to become too large, resulting in poor appearance.

[0039] When the silica fine particles are used, the pore volume of the silica is preferably in the range of 0.5 to 2.0 ml / g, more preferably 0.8 to 1.6 ml / g. If the pore volume is less than 0.5 ml / g, voids are likely to occur, and the transparency of the film is deteriorated. If the pore volume is more than 2.0 ml / g, the fine particles tend not to form surface protrusions.

[0040] The organic lubricant may contain a fatty acid amide and / or a fatty acid bisamide, such as erucic acid amide, stearic acid amide, ethylene bisstearic acid amide, ethylene bisbehenic acid amide, or ethylene bisoleic acid amide. The content of fatty acid amide and / or fatty acid bisamide added to layer B is preferably 0.01 to 0.40% by mass, more preferably 0.05 to 0.30% by mass. If the content of fatty acid amide and / or fatty acid bisamide is less than the above range, the slipping property tends to be deteriorated. On the other hand, if it exceeds the above range, the wettability tends to be deteriorated.

[0041] To improve the slipperiness of the film, polyamide resins other than polyamide 6, such as polyamide MXD6 resin, polyamide 11, polyamide 12 resin, polyamide 66 resin, polyamide 6·12 copolymer resin, polyamide 6·66 copolymer resin, etc., can be added to layer B. Polyamide MXD6 resin is particularly preferred, and it is preferable to add 1 to 10% by mass. If it is less than 1% by mass, the effect of improving the slipperiness of the film is small. If it is more than 10% by mass, the effect of improving the slipperiness of the film becomes saturated. Polyamide MXD6 resin is produced by the polycondensation of metaxylylenediamine and adipic acid. The relative viscosity of polyamide MXD6 is preferably 1.8 to 4.5, and more preferably 2.0 to 3.2. If the relative viscosity is less than 1.8 or more than 4.5, it may be difficult to knead it with the polyamide resin in the extruder.

[0042] When adding fine particles, an organic lubricant, or a polyamide resin such as polyamide-MXD6 resin to layer B for the purpose of improving the slipperiness of the film, it is preferable to reduce the amount of these added to the base layer (layer A), since this results in a film that is excellent in both transparency and slipperiness.

[0043] To improve adhesion, layer B may contain a polyamide resin other than polyamide 6. In this case, copolymer polyamide resins such as polyamide 6·12 copolymer resin and polyamide 6·66 copolymer resin are preferred.

[0044] The layer B of the biaxially oriented polyamide film of the present invention may contain an antioxidant, similar to the layer A.

[0045] In the present invention, the biaxially stretched polyamide film or the base layer (A layer) and the functional layer (B layer) can be added with sub-materials and additives such as lubricants and antioxidants during resin polymerization or melt extrusion in an extruder. A high-concentration master batch can be prepared and added to the polyamide resin during film production. Such known methods can be used.

[0046] [Thickness composition of biaxially oriented polyamide film] The thickness of the biaxially oriented polyamide film in the present invention is not particularly limited, but when used as a packaging material, it is usually 100 μm or less, and a thickness of 5 to 50 μm is generally used, and a thickness of 8 to 30 μm is particularly used.

[0047] In the thickness configuration of each layer of the biaxially stretched polyamide film of the present invention, when the thickness of Layer B accounts for most of the total thickness of the film, the bending pinhole resistance decreases. Therefore, in the present invention, the thickness of Layer A is preferably 50 to 93%, particularly 70 to 93%, of the total thickness of Layer A and Layer B.

[0048] [Method of manufacturing gas barrier polyamide film] The gas barrier polyamide film of the present invention is produced by forming an inorganic thin film layer on the biaxially oriented polyamide film of the present invention by the method described below.

[0049] The biaxially stretched polyamide film of the present invention can be produced by a known production method. For example, a sequential biaxial stretching method or a simultaneous biaxial stretching method can be mentioned. The sequential biaxial stretching method is preferable because it can increase the film production speed and is advantageous in terms of production costs. The method for producing the biaxially stretched polyamide film of the present invention will now be described in further detail. First, the raw material resin is melt-extruded using an extruder, extruded from a T-die into a film, and cast onto a cooling roll and cooled to obtain an unstretched film. The melting temperature of the resin is preferably 200 to 300° C. If it is lower than the above, unmelted matter may occur, resulting in defects and other poor appearance, whereas if it exceeds the above, deterioration of the resin may be observed, resulting in a decrease in molecular weight and a deterioration in appearance.

[0050] The cooling roll temperature is preferably from -30 to 80°C, and more preferably from 0 to 50°C. To obtain an unstretched film by casting the film-like molten material extruded from a T-die onto a rotating cooling drum and cooling it, for example, a method using an air knife or an electrostatic adhesion method in which a static charge is applied can be preferably used. The latter method is particularly preferably used.

[0051] It is also preferable to cool the surface of the cast unstretched film opposite the cooling roll. For example, it is preferable to use a method of contacting the surface of the unstretched film opposite the cooling roll with a cooling liquid in a tank, a method of applying a liquid that evaporates with a spray nozzle, a method of spraying a high-speed fluid, or the like. The unstretched film thus obtained is stretched biaxially to obtain a biaxially stretched polyamide film.

[0052] As a method for stretching in the MD direction, multi-stage stretching such as one-stage stretching or two-stage stretching can be used. As described later, multi-stage MD stretching such as two-stage stretching is preferable in terms of physical properties and uniformity of physical properties in the MD direction and the TD direction (isotropy) rather than one-stage stretching. In the sequential biaxial stretching method, stretching in the MD direction is preferably performed by roll stretching.

[0053] The lower limit of the MD stretching temperature is preferably 50° C., more preferably 55° C., and further preferably 60° C. If the temperature is less than 50° C., the resin does not soften, and stretching may become difficult. The upper limit of the MD stretching temperature is preferably 120° C., more preferably 115° C., and further preferably 110° C. If the temperature exceeds 120° C., the resin becomes too soft and stable stretching may not be possible.

[0054] The lower limit of the stretching ratio in the MD direction (when stretching in multiple stages, the total stretching ratio multiplied by each stretching ratio) is preferably 2.2 times, more preferably 2.5 times, and further preferably 2.8 times. If it is less than 2.2 times, the thickness accuracy in the MD direction decreases, and the crystallinity becomes too low, which may reduce the impact strength. The upper limit of the stretching ratio in the MD direction is preferably 5.0 times, more preferably 4.5 times, and most preferably 4.0 times. If it exceeds 5.0 times, the subsequent stretching may become difficult.

[0055] In addition, when the MD stretching is performed in multiple stages, the above-mentioned stretching is possible in each stretching, but the stretching ratios must be adjusted so that the product of all MD stretching ratios is 5.0 or less. For example, in the case of two-stage stretching, the first stage stretching is preferably 1.5 to 2.1 times, and the second stage stretching is preferably 1.5 to 1.8 times.

[0056] The film stretched in the MD direction is stretched in the TD direction using a tenter, heat-set, and then subjected to a relaxation treatment (also called a relaxation treatment). The lower limit of the TD stretching temperature is preferably 50° C., more preferably 55° C., and further preferably 60° C. If the temperature is less than 50° C., the resin does not soften, and stretching may become difficult. The upper limit of the stretching temperature in the TD direction is preferably 190° C., more preferably 185° C., and further preferably 180° C. If the temperature exceeds 190° C., crystallization may occur, making stretching difficult.

[0057] The lower limit of the stretch ratio in the TD direction (when stretching in multiple stages, the total stretch ratio multiplied by each stretch ratio) is preferably 2.8, more preferably 3.2, even more preferably 3.5, and particularly preferably 3.8. If it is less than 2.8, the thickness accuracy in the TD direction decreases, and the crystallinity becomes too low, which may reduce the impact strength. The upper limit of the stretching ratio in the TD direction is preferably 5.5 times, more preferably 5.0 times, still more preferably 4.7 times, particularly preferably 4.5 times, and most preferably 4.3 times. If it exceeds 5.5 times, the productivity may decrease significantly.

[0058] Selection of the heat setting temperature is an important factor in the present invention. As the heat setting temperature is increased, the crystallization and orientation relaxation of the film progresses, and the heat shrinkage rate can be reduced. On the other hand, when the heat setting temperature is low, the crystallization and orientation relaxation are insufficient, and the heat shrinkage rate cannot be reduced sufficiently.) Moreover, if the heat setting temperature is too high, the resin deteriorates and the film rapidly loses its toughness, such as impact strength.

[0059] The lower limit of the heat setting temperature is preferably 180° C., more preferably 200° C. If the heat setting temperature is too low, the heat shrinkage rate becomes too large, which tends to deteriorate the appearance after lamination and to decrease the laminate strength. The upper limit of the heat setting temperature is preferably 230° C., more preferably 220° C. If the heat setting temperature is too high, the impact strength tends to decrease.

[0060] The heat setting time is preferably 0.5 to 20 seconds. More preferably, it is 1 to 15 seconds. The heat setting time can be set appropriately by taking into account the heat setting temperature and the wind speed in the heat setting zone. If the heat setting conditions are too weak, crystallization and orientation relaxation become insufficient, causing the above problems. If the heat setting conditions are too strong, the film toughness decreases.

[0061] Relaxation treatment after heat setting is effective for controlling the heat shrinkage rate. The temperature for relaxation treatment can be selected within the range from the heat setting temperature to the glass transition temperature (Tg) of the resin, but it is preferably from the heat setting temperature -10°C to Tg +10°C. If the relaxation temperature is too high, the shrinkage speed will be too fast, which is undesirable and may cause distortion. Conversely, if the relaxation temperature is too low, relaxation treatment will not occur and the film will simply slacken, the heat shrinkage rate will not decrease, and dimensional stability will deteriorate.

[0062] The lower limit of the relaxation rate in the relaxation treatment is preferably 0.5%, and more preferably 1%. If it is less than 0.5%, the heat shrinkage rate may not be reduced sufficiently. The upper limit of the relaxation rate is preferably 20%, more preferably 15%, and further preferably 10%. If it exceeds 20%, sagging may occur in the tenter, making production difficult.

[0063] In order to increase the adhesive strength with the sealant film or the printed layer, the surface of the laminated oriented polyamide film may be subjected to a corona treatment, a flame treatment, or the like.

[0064] [Inorganic thin film layer and method for forming same] The gas barrier polyamide film of the present invention can be provided with excellent gas barrier properties by providing an inorganic thin film layer on at least one surface of the biaxially oriented polyamide film of the present invention. The inorganic thin film layer in the gas barrier film of the present invention and the method for forming the same will now be described. The inorganic thin film layer is a thin film made of a metal or an inorganic oxide. There is no particular limitation on the material forming the inorganic thin film layer as long as it can be made into a thin film, but from the viewpoint of transparency and gas barrier properties, inorganic oxides such as silicon oxide (silica), aluminum oxide (alumina), and a mixture of silicon oxide and aluminum oxide are preferred. In particular, a composite oxide of silicon oxide and aluminum oxide is preferred from the viewpoint of achieving both flexibility and denseness of the inorganic thin film layer. In this composite oxide, the mixture ratio of silicon oxide and aluminum oxide is preferably in the range of 20 to 70 mass% Al in terms of the mass ratio of the metal content. If the Al concentration is less than 20 mass%, the water vapor barrier property may be reduced. On the other hand, if it exceeds 70 mass%, the inorganic thin film layer tends to become hard, and the film may be destroyed during secondary processing such as printing or lamination, resulting in a decrease in gas barrier property. Note that silicon oxide here refers to various silicon oxides such as SiO and SiO2 or a mixture thereof, and aluminum oxide refers to various aluminum oxides such as AlO and A12O3 or a mixture thereof.

[0065] The inorganic thin film layer has a thickness of usually 1 to 100 nm, preferably 5 to 50 nm. If the inorganic thin film layer has a thickness of less than 1 nm, it may be difficult to obtain satisfactory gas barrier properties, while if the inorganic thin film layer has a thickness exceeding 100 nm, the corresponding improvement in gas barrier properties cannot be obtained, and it is rather disadvantageous in terms of flex resistance and production costs.

[0066] The method for forming the inorganic thin film layer is not particularly limited, and any known deposition method, such as physical deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, or chemical deposition (CVD), may be appropriately adopted. A typical method for forming the inorganic thin film layer will be described below using a silicon oxide / aluminum oxide thin film as an example. For example, when the vacuum deposition method is adopted, a mixture of SiO2 and Al12O3, or a mixture of SiO2 and Al, is preferably used as the deposition raw material. Particles are usually used as these deposition raw materials, and in this case, it is desirable that the size of each particle is large enough that the pressure during deposition does not change, and the preferred particle diameter is 1 mm to 5 mm. Heating can be performed by resistance heating, high-frequency induction heating, electron beam heating, laser heating, or other methods. It is also possible to introduce oxygen, nitrogen, hydrogen, argon, carbon dioxide, water vapor, or other reactive gases as reaction gases, or to adopt reactive deposition using means such as ozone addition and ion assist. Furthermore, the film formation conditions can be changed arbitrarily, such as applying a bias to the deposition target (laminated film to be subjected to deposition), or heating or cooling the deposition target. The deposition material, reaction gas, bias of the deposition target, heating / cooling, etc. can be changed in the same manner when the sputtering method or the CVD method is adopted.

[0067] [Properties of gas barrier polyamide film] The gas barrier polyamide film laminated with the inorganic thin film of the present invention preferably has 10 or less pinhole defects when a twist bending test is performed 1000 times at a temperature of 1° C. using a Gelbo flex tester according to the measurement method described in the Examples. More preferably, the number is 5 or less. The fewer the number of pinhole defects after the bending test, the better the bending pinhole resistance is. If the number of pinholes is 10 or less, a packaging bag that is less likely to develop pinholes even when a load is applied to the packaging bag during transportation, etc. can be obtained.

[0068] Furthermore, the gas barrier polyamide film of the present invention preferably has a distance until pinholes appear in an abrasion pinhole resistance test of 2900 cm or more, more preferably 3100 cm or more, and even more preferably 3300 cm or more. The longer the distance until pinholes appear, the better the abrasion pinhole resistance is, and if the distance until pinholes appear is 2900 cm or more, a packaging bag that is less likely to have pinholes even if the packaging bag rubs against a cardboard box or the like during transportation can be obtained. The gas barrier polyamide film of the present invention is characterized by having excellent properties in both bending pinhole resistance and friction pinhole resistance. The gas barrier polyamide film according to the embodiment of the present invention having these properties is extremely useful as a packaging film because it is less likely to develop pinholes during transportation.

[0069] The gas barrier polyamide film of the present invention has a heat shrinkage rate at 160°C for 10 minutes in both the machine direction (hereinafter abbreviated as MD direction) and the width direction (hereinafter abbreviated as TD direction) in the range of 0.6 to 3.0%, preferably 0.6 to 2.5%. If the heat shrinkage rate exceeds 3.0%, curling or shrinkage may occur when heat is applied in the next process such as lamination or printing. Furthermore, the lamination strength with the sealant film may be weakened. Although it is possible to make the heat shrinkage rate less than 0.6%, it may become mechanically fragile. Furthermore, this is not preferable because it deteriorates productivity.

[0070] Since excellent impact resistance is a feature of biaxially oriented polyamide films, the impact strength of the gas barrier polyamide film of the present invention is preferably 0.7 J / 15 μm or more, and more preferably 0.9 J / 15 μm or more.

[0071] The haze value of the gas barrier polyamide film of the present invention is preferably 10% or less, more preferably 7% or less, and further preferably 5% or less. A small haze value means good transparency and gloss, so when used for packaging bags, beautiful printing is possible and the product value is increased. Adding fine particles to improve the slipperiness of the film increases the haze value, so the haze value can be reduced by adding fine particles only to the functional layer B.

[0072] The gas barrier polyamide film of the present invention has a radiocarbon content of 100% or more according to ASTM D6866-16. 14 It is preferable that the content of carbon derived from biomass (also called biomass ratio) measured by the FT-IR spectrometer 200 is 1 to 15% based on the total carbon in the polyamide film. Carbon dioxide in the atmosphere contains 14 Since carbon dioxide is contained in the atmosphere at a constant rate (105.5pMC), plants that grow by absorbing carbon dioxide from the atmosphere, such as corn, contain 14 The content is known to be about 105.5 pMC. In addition, C in fossil fuels is 14 It is also known that polyamides contain almost no C. 14 By measuring the ratio of carbon derived from biomass, the ratio of carbon derived from biomass can be calculated.

[0073] The gas barrier polyamide film of the present invention has a laminate strength of 3.0 N / 15 mm or more after being laminated with the polyethylene sealant described in the Examples. The gas barrier polyamide film of the present invention is usually laminated with a sealant film and then processed into a packaging bag. If the laminate strength is 3.0 N / 15 mm or more, when a packaging bag is produced using the highly adhesive polyamide film of the present invention in various lamination configurations, the strength of the seal portion is sufficient, and a strong packaging bag that is difficult to tear can be obtained. In order to increase the lamination strength to 3.0 N / 15 mm or more, the gas barrier polyamide film of the present invention may be subjected to corona treatment, coating treatment, flame treatment, or the like.

[0074] Furthermore, the gas barrier polyamide film of the present invention can be subjected to heat treatment or humidity conditioning treatment to improve dimensional stability depending on the application. In addition, it can also be subjected to corona treatment, coating treatment, flame treatment, etc., or printing processing, etc., to improve the adhesion of the film surface.

[0075] [Laminated film with sealant film] The gas barrier polyamide film of the present invention is laminated with a sealant film or the like to form a laminate film, and then processed into packaging bags such as bottom-sealed bags, side-sealed bags, three-side-sealed bags, pillow bags, standing pouches, gusseted bags, and square-bottom bags. Examples of the sealant film include an unstretched linear low-density polyethylene film, an unstretched polypropylene film, and an ethylene-vinyl alcohol copolymer resin film. The layer structure of the laminated film using the gas barrier polyamide film of the present invention is not particularly limited as long as the gas barrier polyamide film according to the embodiment of the present invention is contained in the laminated film. The film used for the laminated film may be made of either petrochemically derived raw materials or biomass-derived raw materials, but polylactic acid, polyethylene terephthalate, polybutylene succinate, polyethylene, polyethylene furanoate, etc., polymerized using biomass-derived raw materials are preferred in terms of reducing environmental load.

[0076] Examples of layer configurations of laminated films using the gas barrier polyamide film of the present invention, where the boundary between layers is represented by / , include ONY / inorganic thin film layer / adhesive / CPP, PET / adhesive / ONY / inorganic thin film layer / adhesive / LLDPE, PET / adhesive / ONY / inorganic thin film layer / PE / LLDPE, PET / adhesive / ONY / inorganic thin film layer / adhesive / CPP, ONY / inorganic thin film layer / adhesive / PET / adhesive / LLDPE, ONY / inorganic thin film layer / adhesive / PET / PE / LLDPE, ONY / inorganic thin film layer / adhesive / PET / adhesive / CPP, ONY / inorganic thin film layer / PE / LLDPE, ONY / inorganic thin film layer / PE / CPP, OPP / adhesive / ONY / inorganic thin film layer / adhesive / LLDPE, ONY / inorganic thin film layer / adhesive / EVOH / adhesive / LLDPE, ONY / inorganic thin film layer / adhesive / EVOH / adhesive / CPP, CPP / adhesive / ONY / inorganic thin film layer / adhesive / LLDPE, and the like. The abbreviations used in the above layer structure are as follows: ONY / inorganic thin film: gas barrier polyamide film of the present invention, PET: stretched polyethylene terephthalate film, LLDPE: unstretched linear low-density polyethylene film, CPP: unstretched polypropylene film, OPP: stretched polypropylene film, PE: extrusion laminate or unstretched low-density polyethylene film, EVOH: ethylene-vinyl alcohol copolymer resin, Adhesive: adhesive layer that bonds films together. EXAMPLES

[0077] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples. The films were evaluated by the following measurement methods. Unless otherwise specified, the measurements were performed in a measurement room with an environment of 23°C and a relative humidity of 65%. (1) Haze value of film The measurement was performed using a direct reading haze meter manufactured by Toyo Seiki Seisakusho Co., Ltd. in accordance with JIS-K-7105. (2) Film thickness Divide the film into 10 equal parts in the TD direction (for narrow films, divide it so that the width is sufficient to measure the thickness), cut out 100mm films in the MD direction, and condition them for more than 2 hours in an environment with a temperature of 23℃ and a relative humidity of 65%. Using a thickness measuring device made by Tester Sangyo, measure the thickness at the center of each sample, and take the average value as the thickness.

[0078] (3) Biomass content of film The obtained film biomass degree was calculated based on the radiocarbon (C 14 ) measurements were performed. (4) Thermal shrinkage rate of film The heat shrinkage rate was measured according to the following formula in accordance with the dimensional change test method described in JIS C2318, except that the test temperature was 160° C. and the heating time was 10 minutes. Heat shrinkage rate = [(length before treatment - length after treatment) / length before treatment] x 100 (%) (5) Impact strength of film Measurements were performed using a film impact tester manufactured by Toyo Seiki Seisakusho Co., Ltd. The measured values ​​were converted per 15 μm thickness and expressed as J (joules) / 15 μm. (6) Dynamic friction coefficient of film The coefficient of dynamic friction between the outer surfaces of the film rolls was evaluated under the following conditions in accordance with JIS-C2151. The test specimen size was 130 mm wide and 250 mm long, and the test speed was 150 mm / min.

[0079] (7) Pinhole resistance of film when bent The number of pinholes due to bending fatigue was measured by the following method using a Gelbo Flex Tester manufactured by Rigaku Kogyosha. After applying a polyester adhesive to the inorganic thin film layer side of the gas barrier film produced in the examples, a linear low-density polyethylene film (L-LDPE film: Toyobo Co., Ltd., L4102) having a thickness of 40 μm was dry laminated, and aging was performed for 3 days in an environment of 40 ° C to obtain a laminate film. The obtained laminate film was cut into 12 inches × 8 inches, and made into a cylindrical shape with a diameter of 3.5 inches with the L-LDPE film side on the inside, one end of the cylindrical film was fixed to the fixed head side of the Gelbo flex tester and the other end to the movable head side, and the initial gripping distance was set to 7 inches. A flex fatigue was performed 1000 times at a speed of 40 times / min, in which a 440 degree twist was given in the first 3.5 inches of the stroke, and the entire stroke was completed in a linear horizontal motion for the next 2.5 inches, and the number of pinholes generated in the laminate film was counted. The measurement was performed in an environment of 1 ° C. The test film was placed on a filter paper (Advantec, No. 50) with the L-LDPE film side facing down, and the four corners were fixed with cellophane tape (registered trademark). Ink (Pilot ink (product number INK-350-Blue) diluted 5 times with pure water) was applied to the test film and spread over the entire surface using a rubber roller. After wiping off unnecessary ink, the test film was removed, and the number of ink dots on the filter paper was counted as the number of pinholes generated in the bending test. The fewer the number of pinholes, the better the bending pinhole resistance.

[0080] (8) Film abrasion and pinhole resistance A friction test was carried out using a fastness tester (manufactured by Toyo Seiki Seisakusho) according to the following method, and the distance at which pinholes occurred was measured. A test sample was made by folding the same laminate film as that produced in the pinhole resistance evaluation above in quarters to make sharp corners, and rubbing it against the inside of a cardboard box with a fastness tester at an amplitude of 25 cm, an amplitude speed of 30 times / min, and a weight of 100 g. The cardboard used was K280 x P180 x K210 (AF) = (surface liner x core material x backing liner (type of flute)). The pinhole occurrence distance was calculated according to the following procedure. The longer the pinhole occurrence distance, the better the abrasion pinhole resistance. First, a friction test was conducted with an amplitude of 100 times and a distance of 2500 cm. If no pinholes were found, the friction test was conducted with an amplitude of 20 times and a distance of 500 cm increased. If no pinholes were found, the friction test was conducted with an amplitude of 20 times and a distance of 500 cm increased again. This was repeated, and the distance at which a pinhole was found was marked with an X and set as level 1. If a pinhole was found with an amplitude of 100 times and a distance of 2500 cm, the friction test was conducted with an amplitude of 20 times and a distance reduced by 500 cm. If a pinhole was found, the friction test was conducted with an amplitude of 20 times and a distance reduced by 500 cm again. This was repeated, and the distance at which a pinhole was not found was marked with an O and set as level 1. Next, for level 2, if the final result in level 1 was ○, the number of amplitudes was increased by 20 and a friction test was conducted. If a pinhole did not appear, it was marked with an ○, and if a pinhole appeared, it was marked with an ×. If the final result in level 1 was ×, the number of amplitudes was decreased by 20 and a friction test was conducted. If a pinhole did not appear, it was marked with an ○, and if a pinhole appeared, it was marked with an ×. Further, for levels 3 to 20, if the previous level was rated as ○, increase the number of amplitudes by 20 and conduct a friction test; if no pinholes are created, mark it as ○, if a pinhole is created, mark it as ×. If the previous level was rated as ×, reduce the number of amplitudes by 20 and conduct a friction test; if no pinholes are created, mark it as ○, if a pinhole is created, mark it as ×. Repeat this process and mark levels 3 to 20 as ○ or ×. For example, the results shown in Table 1 were obtained. Using Table 1 as an example, we will explain how to find the pinhole occurrence distance. Count the number of O and X trials for each distance. The distance with the most tests was used as the median, and the coefficient was set to 0. For distances longer than that, the coefficient was set to +1, +2, +3... for every 500 cm, and for distances shorter than that, the coefficient was set to -1, -2, -3... for every 500 cm. For all tests from levels 1 to 20, the number of tests in which no holes occurred was compared with the number of tests in which holes occurred, and the friction pinhole occurrence distance was calculated using the following formula for each of the cases A and B. A: In all tests, the number of tests without holes is equal to or greater than the number of tests with holes. Distance at which pinholes occur due to friction = median + 500 x (Σ(coefficient x number of tests where no holes occurred) / number of tests where no holes occurred) + 1 / 2) B: In all tests, the number of tests without holes is less than the number of tests with holes. Distance at which friction pinholes occur = median + 500 x (Σ(coefficient x number of tests with holes) / number of tests with holes) - 1 / 2)

[0081] [Table 1]

[0082] (9) Lamination strength with polyethylene sealant The laminate film prepared in the same manner as described in the explanation of the pinhole resistance evaluation was cut into a strip of 15 mm width × 200 mm length, and one end of the laminate film was peeled off at the interface between the biaxially oriented polyamide film and the linear low-density polyethylene film. Using an autograph (manufactured by Shimadzu Corporation), the laminate strength was measured three times in each of the MD and TD directions under the conditions of a temperature of 23°C, a relative humidity of 50%, a tensile speed of 200 mm / min, and a peel angle of 90°, and the average value was used to evaluate the laminate strength.

[0083] (9) Oxygen permeability The vapor-deposited gas barrier film was measured for oxygen permeability at 23°C and a relative humidity of 65% RH using an oxygen permeability measuring device ("OX-TRAN 2 / 21" manufactured by MOCON) in accordance with JIS K7126-2 Method A. Note that the inorganic thin film surface was set as the oxygen gas side during the measurement.

[0084] (13) Relative viscosity of raw polyamide 0.25 g of polyamide was dissolved in 96% sulfuric acid in a 25 ml measuring flask to a concentration of 1.0 g / dl, and the relative viscosity of the polyamide solution was measured at 20°C. (14) Melting point of raw polyamide In accordance with JIS K7121, a differential scanning calorimeter SSC5200 manufactured by Seiko Instruments Inc. was used to measure in a nitrogen atmosphere at a sample weight of 10 mg, a heating start temperature of 30°C, and a heating rate of 20°C / min, and the endothermic peak temperature (Tmp) was determined as the melting point.

[0085] (Example 1-1) Using an apparatus consisting of an extruder and a 380 mm wide T-die, the following molten resin composition was extruded from the T-die into a film, which was then cast onto a cooling roll whose temperature was controlled at 20°C and electrostatically adhered to obtain an unstretched film having a thickness of 200 μm. Resin composition: A resin composition consisting of 97 parts by mass of polyamide 6 (manufactured by Toyobo Co., Ltd., relative viscosity 2.8, melting point 220°C), 3.0 parts by mass of polyamide 11 (manufactured by Arkema, relative viscosity 2.5, melting point 186°C), 0.45 parts by mass of porous silica microparticles (manufactured by Fuji Silysia Chemical Ltd., average particle size 2.0 μm, pore volume 1.6 ml / g), and 0.15 parts by mass of fatty acid bisamide (ethylene bisstearic acid amide, manufactured by Kyoeisha Chemical Co., Ltd.). The obtained unstretched film was introduced into a roll-type stretching machine, and by utilizing the difference in peripheral speed of the rolls, it was stretched 1.73 times in the MD direction at 80° C., and then further stretched 1.85 times at 70° C. Subsequently, this uniaxially stretched film was continuously introduced into a tenter-type stretching machine, preheated at 110° C., stretched 1.2 times in the TD direction at 120° C., 1.7 times at 130° C., and 2.0 times at 160° C., heat-set at 215° C., relaxed by 7% at 215° C., and then wound up while performing a corona treatment on one side to obtain a biaxially stretched polyamide film. The evaluation results of the obtained biaxially stretched polyamide film are shown in Table 2.

[0086] Next, a thin composite oxide layer of silicon dioxide and aluminum oxide was formed on the corona treated surface of the obtained biaxially oriented polyamide film by the following method. <Formation of inorganic thin film layer made of silicon dioxide and aluminum oxide (SiO2 / A12O3)> An inorganic thin film layer of a composite oxide of silicon dioxide and aluminum oxide was formed on the corona-treated surface of the obtained biaxially stretched polyamide film by electron beam deposition. The deposition method was as follows: the film was set on the unwinding side of a continuous vacuum deposition machine, and the film was wound up by running it over a cooled metal drum. At this time, the continuous vacuum deposition machine was operated for 10 -4 The pressure was reduced to below Torr, and SiO2 particles (purity 99.9%) and Al2O3 (purity 99.9%) of about 3 mm to 5 mm were used as deposition sources in an alumina crucible from the bottom of the cooling drum. The thickness of the resulting inorganic thin film layer (SiO2 / Al2O3 composite oxide layer) was 13 nm. The composition of this composite oxide layer was SiO2 / Al2O3 (mass ratio) = 60 / 40. The evaluation results of the resulting gas barrier polyamide film are shown in Table 2.

[0087] (Examples 1-2 to 1-5) A biaxially stretched polyamide film and a gas barrier polyamide film were obtained in the same manner as in Example 1-1, except that the raw material resin composition was changed as shown in Table 2. The evaluation results of the obtained gas barrier polyamide film are shown in Table 2.

[0088] However, in Examples 1-6 and 1-7, an inorganic thin film layer of aluminum oxide was formed as the inorganic thin film layer by the following method. <Formation of Aluminum Oxide (A12O3) Inorganic Thin Film Layer> An inorganic thin film layer of aluminum oxide was formed on the corona-treated surface of the obtained biaxially stretched polyamide film by electron beam deposition. The aluminum oxide deposition method was such that the film was set on the unwinding side of a continuous vacuum deposition machine, and the film was wound up by running it over a cooled metal drum. At this time, the continuous vacuum deposition machine was operated for 10 -4 The pressure was reduced to below Torr, and 99.99% pure metallic aluminum was loaded into an alumina crucible from the bottom of the cooling drum. The metallic aluminum was heated to evaporate, and oxygen was supplied to the vapor to cause an oxidation reaction, which caused it to adhere and deposit on the film, forming an aluminum oxide film 30 nm thick.

[0089] (Comparative Examples 1-1 to 1-5) A biaxially stretched polyamide film and a gas barrier polyamide film were obtained in the same manner as in Example 1 using the blending compositions of raw materials shown in Table 2. The evaluation results of the obtained gas barrier polyamide film are shown in Table 2. However, in Comparative Example 1-3, the molten resin could not be stably extruded into a film from the T-die, and a homogeneous unstretched film could not be obtained, so that biaxial stretching was not possible. In Comparative Example 1-4, a polyamide elastomer that has been conventionally used as a modifier for improving pinhole resistance to bending was blended. In Comparative Example 1-5, no inorganic thin film layer was formed.

[0090] [Table 2]

[0091] As shown in Table 2, the gas barrier polyamide films of the examples had good pinhole resistance due to bending and pinhole resistance due to friction. In addition, the films had low haze and good transparency, high impact strength, and high lamination strength with a sealant film, making them excellent as packaging films. The gas barrier films in Comparative Examples 1-1 and 1-2, which were biaxially oriented polyamide films not containing a material that improves pinhole resistance on bending and biaxially oriented polyamide films with too little polyamide 11 content and on which an inorganic thin film was formed, had poor pinhole resistance on bending. In Comparative Example 1-3, the content of polyamide 11 was too high, so the molten resin could not be stably extruded into a film from the T-die, and therefore a homogeneous unstretched film could not be obtained, and a biaxially stretched polyamide film could not be obtained. In Comparative Example 1-4, a polyamide elastomer that has been conventionally used as a material for improving pinhole resistance due to bending was used. The gas barrier polyamide film obtained had good pinhole resistance due to bending, but poor pinhole resistance due to friction. In Comparative Example 1-5, since no inorganic thin film layer was formed, the oxygen permeability was high and the product was not suitable for gas barrier packaging.

[0092] (Examples 2-1 to 2-9) A biaxially stretched polyamide film and a gas barrier polyamide film were obtained in the same manner as in Example 1-1, except that the raw material resin composition and the inorganic thin film layer were changed as shown in Table 3. The evaluation results of the obtained gas barrier polyamide film are shown in Table 3. However, in Example 2-6, an inorganic thin film layer of aluminum oxide was formed as the inorganic thin film layer, as in Example 1-6.

[0093] (Comparative Examples 2-1 to 2-5) A biaxially stretched polyamide film and a gas barrier polyamide film were obtained in the same manner as in Example 1 using the blending compositions of raw materials shown in Table 3. The evaluation results of the obtained gas barrier polyamide film are shown in Table 3. However, in Comparative Example 2-2, no inorganic thin film layer was formed. In Comparative Example 2-4, when the content of polyamide 11 as the polyamide resin at least partly derived from biomass was set to 35% by mass, the molten resin could not be stably extruded from the T-die into a film, and a homogeneous unstretched film could not be obtained. Therefore, a biaxially stretched film could not be obtained. In Comparative Example 2-5, a polyamide elastomer that has been conventionally used as a modifier for improving pinhole resistance to bending was blended.

[0094] [Table 3]

[0095] As shown in Table 3, the gas barrier polyamide films of the examples had good pinhole resistance due to bending and pinhole resistance due to friction. In addition, the films had low haze and good transparency, high impact strength, and high lamination strength with a sealant film, making them excellent as packaging films. The gas barrier films formed by forming an inorganic thin film on a biaxially oriented polyamide film (Comparative Example 2-1) that did not contain a material to improve pinhole resistance due to bending, and the biaxially oriented polyamide film (Comparative Example 2-3) that had an excessively low content of polyamide 11, a polyamide resin at least part of which is derived from biomass as a raw material, had poor pinhole resistance due to bending. In Comparative Example 2-2, since no inorganic thin film was formed, the oxygen permeability was high and the gas barrier property was extremely poor. In Comparative Example 2-4, the content of polyamide 11 was too high, so the molten resin could not be stably extruded into a film from the T-die, and therefore a homogeneous unstretched film could not be obtained, and a biaxially stretched polyamide film could not be obtained. In Comparative Example 2-5, a polyamide elastomer that has been conventionally used as a material for improving pinhole resistance due to bending was used. The gas barrier polyamide film obtained had good pinhole resistance due to bending, but poor pinhole resistance due to friction.

[0096] (Example 3-1) Using an apparatus consisting of two extruders and a 380 mm wide co-extrusion T-die, the layers were laminated in a B layer / A layer / B layer configuration using the feed block method, and the molten resin was extruded from the T-die into a film. The film was then cast onto a cooling roll controlled at 20°C and electrostatically adhered to obtain an unstretched film with a thickness of 200 μm. The resin compositions of layers A and B are as follows. Resin composition constituting layer A: a polyamide resin composition consisting of 97 parts by mass of polyamide 6 (manufactured by Toyobo Co., Ltd., relative viscosity 2.8, melting point 220°C) and 3.0 parts by mass of polyamide 11 (manufactured by Arkema, relative viscosity 2.5, melting point 186°C). Resin composition constituting layer B: a resin composition consisting of 95 parts by mass of polyamide 6 (manufactured by Toyobo Co., Ltd., relative viscosity 2.8, melting point 220°C), 5.0 parts by mass of polyamide MXD6 (manufactured by Mitsubishi Gas Chemical Co., Ltd., relative viscosity 2.1, melting point 237°C), 0.54 parts by mass of porous silica fine particles (manufactured by Fuji Silysia Chemical Ltd., average particle size 2.0 μm, pore volume 1.6 ml / g), and 0.15 parts by mass of fatty acid bisamide (ethylene bisstearic acid amide, manufactured by Kyoeisha Chemical Co., Ltd.). The feed block configuration and the extrusion rate of the extruder were adjusted so that the total thickness of the biaxially oriented polyamide film was 15 μm, the thickness of the base layer (layer A) was 12 μm, and the thicknesses of the front and back surface layers (layer B) were each 1.5 μm. The obtained unstretched film was introduced into a roll-type stretching machine, and by utilizing the difference in peripheral speed of the rolls, it was stretched 1.73 times in the MD direction at 80° C., and then further stretched 1.85 times at 70° C. Subsequently, this uniaxially stretched film was continuously introduced into a tenter-type stretching machine, preheated at 110° C., stretched 1.2 times in the TD direction at 120° C., 1.7 times at 130° C., and 2.0 times at 160° C., heat-set at 215° C., relaxed by 7% at 215° C., and then wound up while performing a corona treatment on one side to obtain a biaxially stretched polyamide film. Next, a composite oxide thin film layer of silicon dioxide and aluminum oxide was formed on the corona-treated surface of the obtained biaxially stretched polyamide film in the same manner as in Example 1-1.

[0097] (Example 3-2 to Example 3-9) A biaxially stretched polyamide film and a gas barrier polyamide film were obtained in the same manner as in Example 3-1, except that the raw material resin composition was changed as shown in Table 4. The evaluation results of the obtained gas barrier polyamide film are shown in Table 4. However, in Examples 3-6 and 3-7, an inorganic thin film layer of aluminum oxide was formed as the inorganic thin film layer, similarly to Example 1-6.

[0098] (Comparative Examples 3-1 to 3-5) A biaxially stretched polyamide film and a gas barrier polyamide film were obtained in the same manner as in Example 3-1 using the blending compositions of raw materials shown in Table 4. The evaluation results of the obtained gas barrier polyamide film are shown in Table 4. However, in Comparative Example 3-3, the molten resin could not be stably extruded into a film shape from the T-die, and a homogeneous unstretched film could not be obtained, and therefore a biaxially stretched polyamide film could not be obtained. In Comparative Example 3-4, a polyamide elastomer that has been conventionally used as a modifier for improving pinhole resistance to bending was blended. In Comparative Example 3-5, no inorganic thin film layer was formed.

[0099] [Table 4]

[0100] As shown in Table 4, the gas barrier film having the inorganic thin film layer of the embodiment had good pinhole resistance due to bending and good pinhole resistance due to friction. In addition, the film had low haze, good transparency, and good slipperiness. The film also had high impact strength and high lamination strength with the sealant film, making it an excellent film for packaging. The gas barrier films obtained from the biaxially stretched polyamide film containing no polyamide 11 of Comparative Example 3-1 and the biaxially stretched polyamide film with a low polyamide 11 content of Comparative Example 3-2 were poor in pinhole resistance under bending. In Comparative Example 3-3, the content of polyamide 11 was too high, so the molten resin could not be stably extruded into a film from the T-die, and therefore a homogeneous unstretched film could not be obtained, and a biaxially stretched polyamide film could not be obtained. In Comparative Example 3-4, when a conventional polyamide elastomer was used as a material for improving pinhole resistance, the pinhole resistance was good but the pinhole resistance against friction was poor. In addition, there was a drawback that deterioration materials were easily attached to the die during long-term production, making it impossible to carry out long-term continuous production. In Comparative Example 3-5, since no inorganic thin film layer was formed, the oxygen permeability was high and the product was not suitable for gas barrier packaging.

[0101] (Examples 4-1 to 4-10) A biaxially stretched polyamide film and a gas barrier polyamide film were obtained in the same manner as in Example 3-1, except that the raw material resin composition and the inorganic thin film layer were changed as shown in Table 5. The evaluation results of the obtained gas barrier polyamide film are shown in Table 5. However, in Example 4-8, an inorganic thin film layer of aluminum oxide was formed as the inorganic thin film layer, as in Example 1-6.

[0102] (Comparative Examples 1 to 6) A biaxially stretched polyamide film and a gas barrier polyamide film were obtained in the same manner as in Example 4-1 using the blending compositions of raw materials shown in Table 5. The evaluation results of the obtained gas barrier polyamide films are shown in Table 2. In Comparative Example 4-2, the inorganic thin film layer was not formed in Comparative Example 4-1. In Comparative Example 4-4, the molten resin could not be stably extruded into a film from the T-die, and a homogeneous unstretched film could not be obtained, so that biaxial stretching was not possible. In Comparative Example 4-5, the feed block configuration and the extruder output were adjusted so that the total thickness of the film was 15 μm, the thickness of the base layer (layer A) was 4 μm, and the thicknesses of the front and back surface layers (layer B) were each 5.5 μm, and the proportion of the thickness of the base layer to the total was 20%. In Comparative Example 4-6, a polyamide-based elastomer (PEBAX4033SA02, manufactured by Arkema) that has been conventionally used as a modifier for improving pinhole resistance to bending was blended.

[0103] [Table 5]

[0104] As shown in Table 5, the gas barrier polyamide films of the Examples had low oxygen permeability and excellent gas barrier properties, and also had excellent resistance to pinholes caused by bending and pinholes caused by friction. In addition, the films had low haze and good transparency, and had high lamination strength with a sealant film, making them excellent as packaging films. In Comparative Examples 4-1 and 4-2, the base layer did not contain a polyamide resin whose raw material was at least partly derived from biomass, and in Comparative Example 4-3, the content of polyamide 11 was too low, and the pinhole resistance was poor. In Comparative Example 2, the inorganic thin film layer was not formed, and therefore the oxygen permeability was high. In Comparative Example 4-4, the content of polyamide 11 was too high, so the molten resin could not be stably extruded into a film from the T-die, and therefore a homogeneous unstretched film could not be obtained, and a biaxially stretched polyamide film could not be obtained. In Comparative Example 4-5, the ratio of the thickness of the base layer (A layer) was small, and therefore the bending pinhole resistance was poor. In Comparative Example 4-6, a polyamide elastomer that has been conventionally used as a material for improving pinhole resistance was used. The gas barrier polyamide film obtained had good pinhole resistance but poor pinhole resistance due to friction. [Industrial Applicability]

[0105] The gas barrier polyamide film of the present invention is a gas barrier film having excellent pinhole resistance due to bending and abrasion pinhole resistance at the same time, and therefore can be suitably used for packaging materials requiring gas barrier properties such as food packaging, etc. Furthermore, since the film uses a resin polymerized from raw materials derived from biomass that is originally on the ground, it is a carbon-neutral film and can reduce the environmental load by having little effect on the increase or decrease of carbon dioxide on the ground.

Claims

1. A gas barrier polyamide film characterized by having an inorganic thin film layer on at least one side of a biaxially oriented polyamide film in which the functional layer (B layer) described below is laminated on both sides of the base layer (A layer) described below. The base layer (A layer) contains 99 to 70 mass % of polyamide 6 resin and 1 to 30 mass % of polyamide resin at least partly derived from biomass, the polyamide resin at least partly derived from biomass being at least one polyamide resin selected from the group consisting of polyamide 11, polyamide 410, polyamide 610, and polyamide 1010, and the functional layer (B layer) contains 70 mass % or more of polyamide 6 resin.

2. The radioactive carbon (C 14 2. The gas barrier polyamide film according to claim 1, wherein the content of carbon derived from biomass is 1 to 15% as measured by a carbon dioxide gas saturation test.

3. 3. The gas barrier polyamide film according to claim 1, which satisfies the following (a) and (b): (a) the number of Gelbo pinhole defects is 10 or less when a twisting and bending test using a Gelbo flex tester is performed 1,000 times at a temperature of 1° C.; (b) In the abrasion pinhole resistance test, the distance until pinholes appear is 2,900 cm or more.

4. 4. The gas barrier film according to claim 1, wherein the inorganic thin film layer is a layer made of aluminum oxide or a composite oxide of silicon oxide and aluminum oxide.

5. A laminated film comprising the gas barrier polyamide film according to any one of claims 1 to 4 and a sealant film laminated thereon.

6. A packaging bag using the laminated film according to claim 5.

Citation Information

Patent Citations

  • Biaxially oriented polyamide film and production thereof

    JP1996047972A

  • Biaxially oriented polyamide film

    JP1996198981A

  • Magnetic recording medium

    JP1997007163A

  • Gas barrier resin film

    JP1998029264A

  • Polyamide laminated film

    JP1999254615A